Green catalyst Fe(OTs)(3)/SiO2 for the synthesis of 4-Pyrrolo-12-oxoquinazolines - Allaka, Bhargava Sai; Basavoju, Srinivas; Krishna, Gamidi Rama (ChemistrySelect, 2020)
An efficient and eco-friendly diversity-oriented synthetic protocol has been presented to synthesize structurally versatile drug-like molecules under solvent-free grinding in the presence of Fe(OTs)(3)/SiO2 as a catalyst. The use of Fe(OTs)(3)/SiO2 as a recyclable and reusable catalyst has been explored in the synthetic domino protocol involving one-pot, three component reaction for the synthesis of 4-pyrrolo-12-oxoquinazolines with special features of the protocol like high atom-economy, operational simplicity, short reaction time and high selectivity with excellent yields.
Keywords: 4-Pyrrolo-12-oxoquinazolines; Fe(OTs)(3); Green methodology; Liquid Assisted Grinding (LAG); SiO2 catalyst; Solvent-free grinding